Disseminated Coccidioidomycosis: Cutaneous, Soft Tissue, Osseous, and "Shotgun Intraparenchymal" Brain Disease - Saman Sharifi MS4; Rupam Sharma MD; Arash Heidari MD; Royce H. Johnson MD (SAGE Publishing, 2022)
Coccidioidomycosis is a disease found in the southwestern United States and caused by inhalation of arthroconidia of Coccidioides immitis and posadasii . Although the disease is most commonly asymptomatic or respiratory, it has a propensity to disseminate to any tissue in the body with the most common being skin, bone, joints, and central nervous system. This case demonstrates the dissemination of coccidioidomycosis to several foci along with a rare form of parenchymal dissemination with an unusual neuroradiological finding.